2016
DOI: 10.1055/s-0036-1579631
|View full text |Cite
|
Sign up to set email alerts
|

Osteolysis and Cervical Cord Compression Secondary to Silicone Granuloma Formation around a Dorsal Spinal Cord Stimulator: A Case Report

Abstract: Spinal cord stimulators (SCSs) have long been in use as a modality for the management of numerous pain pathologies. Along with commonly anticipated morbidities such as displacement, failure (due to fracture or breakage), or infection, there have also been rare but well-documented complications of fibrous scarring, resulting in spinal cord compression. This is the first known case that demonstrates osteolysis and bony destruction of the vertebrae adjacent to the SCS along with the foreign-body granulomatous rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…8,60 In orthopedics, the single case study of a silicone-based spinal implant resulted in histopathologic results consistent with a foreign-body reaction (ie, a silicone granulomatous reaction). 61 The author points out this case of biological reaction to spinal cord stimulator cover particle shedding is consistent with other cases of foreign-body reactions to silicone particles, including BI particles. 62-64 Differences in innate immune cell behavior such as resident tissue macrophages (histiocytes) between the breast and other areas such as the hip or knee can be influenced by their environment and thus may be more (or less) likely to induce inflammatory responses to particle challenge.…”
Section: Local Inflammatory Effects Of Implant Debrissupporting
confidence: 78%
“…8,60 In orthopedics, the single case study of a silicone-based spinal implant resulted in histopathologic results consistent with a foreign-body reaction (ie, a silicone granulomatous reaction). 61 The author points out this case of biological reaction to spinal cord stimulator cover particle shedding is consistent with other cases of foreign-body reactions to silicone particles, including BI particles. 62-64 Differences in innate immune cell behavior such as resident tissue macrophages (histiocytes) between the breast and other areas such as the hip or knee can be influenced by their environment and thus may be more (or less) likely to induce inflammatory responses to particle challenge.…”
Section: Local Inflammatory Effects Of Implant Debrissupporting
confidence: 78%
“…In many cases, the biopsies show the presence of macrophages with internalized foreign material from the implant, as has been reported for a pin made up of PLGA 176 and for a silicone implant, which was used as a spinal cord stimulator. 177 The particulate matter from the implant was identified as the cause of the reaction, which occurred as late as 10 years after implantation. Another case study also reported a delayed degradation response to PLLA after 11 months.…”
Section: Interactionmentioning
confidence: 99%
“…29 Rupture can result in an abnormal contour of the breast, breast lumps, capsular contracture, 25 local inflammation, and potentially dissemination of silicone. [2][3][4][5][6][7][8][9][10][11][12] Despite intense scrutiny regarding the safety and efficacy of silicone breast implants, limited literature regarding migration of silicone from breast implants to the eyelids has been described. Prior cases include that reported by Meyer et al, describing silicone oil bleeding, and a case reported by Chen et al, featuring disseminated silicone due to bilateral occult rupture of silicone implants.…”
Section: Silicone Breast Implantsmentioning
confidence: 99%
“…The pathology of silicone leakage was first thoroughly described in 1998 2 and migration has subsequently been detected to nearly every part of the body. [2][3][4][5][6][7][8][9][10][11][12] Similarly, there are numerous reports of migration of liquid silicone used for soft tissue enhancement away from the primary site of injection or implantation. [13][14][15] However, migratory silicone oil to the eyelids or orbit from either breast implants or silicone-based filler has been rarely reported in the ophthalmic literature; the mechanisms of dissemination are also incompletely understood.…”
mentioning
confidence: 99%